Little grey (Grasindo, 2018)
Little grey is different from other girls. Her hair is as grey as the ashes, and her only friend is Zooey, the grey cat. Everyone calls her 'little grey'. Until one day, she meets new friend who calls her as 'Anna', her real name.....